TELEHEALTH: YOUR PATH TO EFFICIENT, EFFECTIVE, AND ACCESSIBLE CARE - Mohammed Shadab Aslam; Dr. Sakhi John (PT. Radja Intercontinental Publishing, 2023)
ABSTRACT Telehealth has emerged as a transformative force in the healthcare industry, offering new pathways to deliver efficient, effective, and accessible care. This paper explores the evolution, impact, and potential future growth of telehealth. We examine the technological, regulatory, and patient-centric aspects of telehealth to shed light on how it is revolutionizing the delivery of healthcare services. Through case studies and an analysis of challenges and limitations, this paper outlines the hurdles and opportunities for telehealth in the evolving healthcare landscape